TPC1 deficiency or blockade augments systemic anaphylaxis and mast cell activity - Arlt, Elisabeth; Tsvilovskyy, Volodymyr; Freichel, Marc (Proceedings of the National Academy of Sciences of the United States of America, 2020)
Mast cells and basophils are main drivers of allergic reactions and anaphylaxis, for which prevalence is rapidly increasing. Activation of these cells leads to a tightly controlled release of inflammatory mediators stored in secretory granules. The release of these granules is dependent on intracellular calcium (Ca2+) signals. Ca2+ release from endolysosomal compartments is mediated via intracellular cation channels, such as two-pore channel (TPC) proteins. Here, we uncover a mechanism for how TPC1 regulates Ca2+ homeostasis and exocytosis in mast cells in vivo and ex vivo. Notably, in vivo TPC1 deficiency in mice leads to enhanced passive systemic anaphylaxis, reflected by increased drop in body temperature, most likely due to accelerated histamine-induced vasodilation. Ex vivo, mast cell-mediated histamine release and degranulation was augmented upon TPC1 inhibition, although mast cell numbers and size were diminished. Our results indicate an essential role of TPC1 in endolysosomal Ca2+ uptake and filling of endoplasmic reticulum Ca2+ stores, thereby regulating exocytosis in mast cells. Thus, pharmacological modulation of TPC1 might blaze a trail to develop new drugs against mast cell-related diseases, including allergic hypersensitivity.
Published first July 13, 2020
Gesehen am 28.09.2020